Cost-effectiveness of point-of-care creatinine testing to assess kidney function prior to contrast-enhanced computed tomography imaging. Issue 142 (September 2021) - Duarte, Ana; Walker, Simon; Altunkaya, James; Dias, Sofia; Corbett, Mark; Llewellyn, Alexis; Harris, Martine A.; Palmer, Stephen; Soares, Marta
Highlights: A testing sequence including Point-of-care creatinine (POC) may be cost-effective. This sequence combines risk factor screening with a POC test and laboratory testing. The cost-effectiveness of POC tests is driven by cost-savings in the health system. This potential savings stem from avoided CT scan delays to CT scans. The risk of PC-AKI from contrast and the effect of IV hydration remain uncertain. Abstract: Background: Patients undergoing contrast-enhanced computed tomography (CECT) imaging in a non-emergency outpatient setting often lack a recent estimated Glomerular Filtration Rate measurement. This may lead to inefficiencies in the CECT pathway. The use of point-of-care (POC) creatinine tests to evaluate kidney function in these patients may provide a safe and cost-effective alternative to current practice, as these can provide results within the same CECT appointment. Methods: A decision tree model was developed to characterise the diagnostic pathway and patient management (e.g., intravenous hydration) and link these to adverse renal events associated with intravenous contrast media. Twelve diagnostic strategies including three POC devices (i-STAT, ABL800 Flex and StatSensor), risk factor screening and laboratory testing were compared with current practice. The diagnostic accuracy of POC devices was derived from a systematic review and meta‐analysis; relevant literature sources and databases informed other parameters. The cost-effective strategy from a health care perspective was identified based on highest net health benefit (NHB) which were expressed in quality-adjusted life years (QALYs) at £20, 000/QALY. Results: The cost-effective strategy, with a NHB of 9.98 QALYs and a probability of being cost-effective of 79.3%, was identified in our analysis to be a testing sequence involving screening all individuals for risk factors, POC testing (with i-STAT) on those screening positive, and performing a confirmatory laboratory test for individuals with a positive POC result. The incremental NHB of this strategy compared to current practice, confirmatory laboratory test, is 0.004 QALYs. Results were generally robust to scenario analysis. Conclusions: A testing sequence combining a risk factor questionnaire, POC test and confirmatory laboratory testing appears to be cost-effective compared to current practice. The cost-effectiveness of POC testing appears to be driven by reduced delays within the CECT pathway. The contribution of intravenous contrast media to acute kidney injury, and the benefits and harms of intravenous hydration remain uncertain.